(untitled) (International journal of artificial intelligence, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. It is one of the most prevalent non-communicable diseases globally, affecting millions of people and leading to significant morbidity and mortality. The main types of diabetes include Type 1 diabetes mellitus (T1DM), an autoimmune destruction of pancreatic beta cells; Type 2 diabetes mellitus (T2DM), characterized by insulin resistance and relative insulin deficiency; gestational diabetes, which occurs during pregnancy; and other less common forms, including monogenic diabetes and secondary diabetes due to endocrine disorders or medication. The pathogenesis of diabetes is complex and multifactorial. In T1DM, genetic susceptibility and environmental triggers lead to autoimmune beta-cell destruction, resulting in absolute insulin deficiency. In T2DM, obesity, sedentary lifestyle, and genetic factors contribute to insulin resistance, beta-cell dysfunction, and chronic low-grade inflammation. Chronic hyperglycemia in diabetes results in microvascular complications, such as retinopathy, nephropathy, and neuropathy, and macrovascular complications, including cardiovascular disease and stroke. Management of diabetes requires a multidisciplinary approach encompassing lifestyle interventions, pharmacological therapy, and patient education. Lifestyle measures include dietary modifications, regular physical activity, weight management, and smoking cessation. Pharmacological therapy involves insulin administration for T1DM and individualized oral or injectable antidiabetic agents for T2DM, targeting glycemic control, cardiovascular risk reduction, and prevention of complications. Recent advances in therapy include GLP-1 receptor agonists, SGLT2 inhibitors, and continuous glucose monitoring systems, which improve patient outcomes and quality of life. This review aims to provide a comprehensive overview of the types of diabetes mellitus, underlying pathogenic mechanisms, common complications, and current treatment strategies. Understanding the pathophysiology and individualized management of diabetes is crucial for reducing disease burden and improving long-term patient outcomes.